2022
DOI: 10.1021/acs.iecr.2c00196
|View full text |Cite
|
Sign up to set email alerts
|

Acid Gas Removal by Superhigh Silica ZSM-5: Adsorption Isotherms of Hydrogen Sulfide, Carbon Dioxide, Methane, and Nitrogen

Abstract: The adsorption of acid gas, including hydrogen sulfide and carbon dioxide, by superhigh silica ZSM-5 was investigated. Equilibrium adsorption isotherms of high-purity hydrogen sulfide and carbon dioxide were measured experimentally using this new sorbent. In addition, methane and nitrogen adsorption isotherms on this MFI-type zeolite were also measured as representative of other natural gas components. To enhance the reliability of the results, the adsorption pressure has been selected up to 20 bar at three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…21,22 Therefore, MFI is one of the best options to remove H 2 S. Zeolite Socony Mobil -5 (ZSM-5) is a crystalline substance, which belongs to the MFI category that has a porous structure, and has been reported to be commonly employed to trap molecules. 23 Zeolites are known to be molecular sieves since they have high porosity. 24 In both gaseous and aqueous settings, ZSM-5 has the ability to adsorb and eliminate hydrogen sulphide (H 2 S).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Therefore, MFI is one of the best options to remove H 2 S. Zeolite Socony Mobil -5 (ZSM-5) is a crystalline substance, which belongs to the MFI category that has a porous structure, and has been reported to be commonly employed to trap molecules. 23 Zeolites are known to be molecular sieves since they have high porosity. 24 In both gaseous and aqueous settings, ZSM-5 has the ability to adsorb and eliminate hydrogen sulphide (H 2 S).…”
Section: Introductionmentioning
confidence: 99%
“…In the actual situation, the mixed gases entering the adsorption separation step will contain a certain amount of water vapor. Hydrophobic sorbents, such as high-silicon zeolites, have been investigated in detail. Rahmani et al measured the equilibrium adsorption isotherms of acid gases (H 2 S, CO 2 , CH 4 , and N 2 ) on superhigh-silica ZSM-5 zeolite with Si/Al = 3000. Li’s group tested the homemade zeolite silicalite-1 to separate CH 4 and N 2 by the PSA process and confirmed that the effect of water vapor could be negligible.…”
Section: Introductionmentioning
confidence: 99%